Shop drawing of hidden framing glass curtain wall (aluminum clad steel) of section 3 (SF01-SF05) (RFA-010_Rev D) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.